Engineered neurogenesis in naïve adult rat cortex by Ngn2-mediated neuronal reprogramming of resident oligodendrocyte progenitor cells - Bazarek, Stanley F.; Thaqi, Mentor; King, Patrick; Mehta, Amol R.; Patel, Ronil; Briggs, Clark A.; Reisenbigler, Emily; Yousey, Jonathon E.; Miller, Elis A.; Stutzmann, Grace E.; Marr, Robert A.; Peterson, Daniel A. (Frontiers in Neuroscience, 2023)
Adult tissue stem cells contribute to tissue homeostasis and repair but the long-lived neurons in the human adult cerebral cortex are not replaced, despite evidence for a limited regenerative response. However, the adult cortex contains a population of proliferating oligodendrocyte progenitor cells (OPCs). We examined the capacity of rat cortical OPCs to be re-specified to a neuronal lineage both in vitro and in vivo. Expressing the developmental transcription factor Neurogenin2 (Ngn2) in OPCs isolated from adult rat cortex resulted in their expression of early neuronal lineage markers and genes while downregulating expression of OPC markers and genes. Ngn2 induced progression through a neuronal lineage to express mature neuronal markers and functional activity as glutamatergic neurons. In vivo retroviral gene delivery of Ngn2 to naive adult rat cortex ensured restricted targeting to proliferating OPCs. Ngn2 expression in OPCs resulted in their lineage re-specification and transition through an immature neuronal morphology into mature pyramidal cortical neurons with spiny dendrites, axons, synaptic contacts, and subtype specification matching local cytoarchitecture. Lineage respecification of rat cortical OPCs occurred without prior injury, demonstrating these glial progenitor cells need not be put into a reactive state to achieve lineage reprogramming. These results show it may be feasible to precisely engineer additional neurons directly in adult cerebral cortex for experimental study or potentially for therapeutic use to modify dysfunctional or damaged circuitry.